2013
DOI: 10.4187/respcare.02518
|View full text |Cite
|
Sign up to set email alerts
|

Nebulization During Spontaneous Breathing, CPAP, and Bi-Level Positive-Pressure Ventilation: A Randomized Analysis of Pulmonary Radioaerosol Deposition

Abstract: BACKGROUND: There have been few reports of factors affecting aerosol delivery during noninvasive ventilation (NIV). Nebulization is a standard practice, and our objective was to determine the effect of spontaneous breathing (SB) and NIV mode on lung technetium-99m (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
(40 reference statements)
0
8
0
3
Order By: Relevance
“…It was thought that this reduction in lung dose of bronchodilators using this modality of ventilation would reduce bronchodilator efficacy in relieving bronchial obstruction. In contrast, Maccari et al 31 recently reported similar lung counts after administration of a jet nebulizer with spontaneous breathing, CPAP at 10 cm H 2 O, and BPAP at 15/5 cm H 2 O. They reported counts (mean Ϯ SD) in the right lung of 196 Ϯ 167 with spontaneous breathing, 109 Ϯ 40 with CPAP, and 112 Ϯ 15 with BPAP, with a similar trend in the left lung of 225 Ϯ 293, 93 Ϯ 15, and 98 Ϯ 14, respectively.…”
Section: Discussionmentioning
confidence: 83%
“…It was thought that this reduction in lung dose of bronchodilators using this modality of ventilation would reduce bronchodilator efficacy in relieving bronchial obstruction. In contrast, Maccari et al 31 recently reported similar lung counts after administration of a jet nebulizer with spontaneous breathing, CPAP at 10 cm H 2 O, and BPAP at 15/5 cm H 2 O. They reported counts (mean Ϯ SD) in the right lung of 196 Ϯ 167 with spontaneous breathing, 109 Ϯ 40 with CPAP, and 112 Ϯ 15 with BPAP, with a similar trend in the left lung of 225 Ϯ 293, 93 Ϯ 15, and 98 Ϯ 14, respectively.…”
Section: Discussionmentioning
confidence: 83%
“…The objective of the study by Maccari 18 et al was to determine the effect of spontaneous breathing and NIV on lung technetium-99m deposition in subjects with normal lungs. The study enrolled 13 volunteers for technetium radioaerosol nebulization during spontaneous breathing, CPAP at 10 cm H 2 O, and bi-level ventilation with inspiratory and expiratory pressures of 15 and 5 cm H 2 O.…”
Section: Healthy Volunteersmentioning
confidence: 99%
“…Die Effektivität der Gabe von inhalativen Medikamenten während der Maskenbeatmung hängt von vielen Faktoren ab, so beeinflussen die Beatmungsdrücke, das Ausatemsystem [103] und der Ort der Applikation die Wirksamkeit [104,105]. Grundsätzlich ist bei korrektem Inhalationsmanöver die pulmonale Deposition bei Spontanatmung besser als unter NIV.…”
Section: Inhalationunclassified